MANAGEMENT OF INNOVATION IN THE SPHERE OF HUMAN CAPITAL AND LOGISTICS ACTIVITIES OF AN ENTERPRISE IN THE CONDITIONS OF SOCIO-ECONOMIC TRANSFORMATIONS - MYKYTYUK, Petro; HREITSAR, Maksym; HREITSAR, Serhii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Modern socio-economic transformations require enterprises to continuously adapt their management systems to the dynamic conditions of the global market. In an era characterized by rapid globalization, digital transformation, and intensified competition, the development of innovative mechanisms for managing enterprise growth has become an essential factor for long-term sustainability and competitiveness. Companies must not only react to changes but proactively form adaptive strategies based on innovation, digitalization, and the effective use of internal resources. Among the most significant determinants of this process are the efficient management of human capital and the modernization of logistics activities, which together determine the overall performance and resilience of an organization.Human capital represents the key strategic resource of any enterprise — the bearer of knowledge, creativity, and professional competencies that ensure innovation and organizational renewal. Managing human capital involves developing employees’ potential through education, motivation, and digital skills enhancement, fostering an innovative corporate culture capable of responding flexibly to challenges. Effective human resource management not only increases productivity but also strengthens the organization’s ability to implement technological innovations and maintain competitive advantages in the long term.Logistics, in turn, functions as a critical infrastructure element connecting production, supply, and distribution systems. Its modernization through digital technologies, automation, and data-driven decision-making enables companies to optimize material, information, and financial flows. Implementing smart logistics systems, artificial intelligence, and predictive analytics allows enterprises to reduce costs, minimize risks, and improve customer satisfaction.The integration of innovative approaches in human capital management and logistics creates a powerful synergistic effect, enhancing efficiency across all operational levels. This synergy ensures sustainable enterprise development, promotes digital transformation, and facilitates the formation of new competitive advantages in the global economy. Therefore, the study of innovation management in these interrelated domains is of high theoretical and practical significance for modern business.
Keywords: innovation; management; human capital; logistics activities; innovation mechanism; competitiveness; socio-economic transformations; digitalization; innovative development; logistics quality